Social Construction Of Justice In Refereeing In The Amateur Football Community In Sinjai District - Gunawan, Muh. Rizal; Usman, Arifuddin; Hudain, Muh. Adnan (UNIVERSITAS NEGERI MAKASSAR, 2025)
Fairness in refereeing is an important element that greatly influences the course of a football match, including at the amateur community level. In Sinjai Regency, the amateur football community is developing quite actively. In this context, perceptions of referee fairness can play a big role in shaping social dynamics between various actors, such as players, coaches, referees, and supporters. Therefore, this study aims to examine how the social construction of justice in refereeing is formed in the amateur football environment in Sinjai Regency. The main focus of this study is individual perception, personal experience, as well as patterns of social interaction that occur during matches. This research was conducted using a quantitative approach and descriptive method. The research participants consisted of 40 people, including players, coaches, referees, and spectators, who were purposively selected. Data collection instruments included questionnaires and structured interviews, which were designed to gain a deeper understanding of their views on fairness in refereeing. The results showed that most respondents (75%) had a positive view of referee fairness, while 25% were neutral. In addition, 90% of respondents stated that they had good experiences with referees, while the rest were neutral. These findings indicate that refereeing in this community is effective, although further evaluation and training are needed to strengthen the objectivity and consistency of referee decisions in the future.